2006
DOI: 10.1039/b612064b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic standing wave manipulation technology integrated into a dielectrophoretic chip

Abstract: Several cell-based biological applications in microfluidic systems require simultaneous high-throughput and individual handling of cells or other bioparticles. Available chip-based tools for contactless manipulation are designed for either high-precision handling of individual particles, or high-throughput handling of ensembles of particles. In order to simultaneously perform both, we have combined two manipulation technologies based on ultrasonic standing waves (USWs) and dielectrophoresis (DEP) in a microflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 45 publications
1
80
0
Order By: Relevance
“…To date, many acoustic-based particle manipulation functions (e.g., focusing, separating, sorting, mixing, and patterning) have been realized (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). None of these approaches, however, have achieved the dexterity of optical tweezers; in other words, none of the previous acoustic-based methods are capable of precisely manipulating single microparticles or cells along an arbitrary path in two dimensions.…”
mentioning
confidence: 99%
“…To date, many acoustic-based particle manipulation functions (e.g., focusing, separating, sorting, mixing, and patterning) have been realized (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). None of these approaches, however, have achieved the dexterity of optical tweezers; in other words, none of the previous acoustic-based methods are capable of precisely manipulating single microparticles or cells along an arbitrary path in two dimensions.…”
mentioning
confidence: 99%
“…Wiklund et al 44 first demonstrated the integration of both acoustophoretic and DEP particle manipulation within a microfluidic device, as shown in Figure 5. Acoustic standing waves were set up across the width of the channel, to assemble linear arrays and aggregates of particles, which could then be further manipulated by DEP produced by co-planar electrodes at the bottom of the channel.…”
Section: Forces Induced By Electrical Fieldsmentioning
confidence: 99%
“…Other ways to obtain separation is by displacing the particles in the out-of-plane direction 33 or by exciting a fluid channel mode by an external transducer. 22,34 In order to manipulate cells individually in a flow, the acoustic energy needs to be localized to a small zone as is obtained for the integrated miniaturized transducers.…”
Section: Introductionmentioning
confidence: 99%